The Effect Of The Whistleblowing System And Tax Sanctions On Individual Taxpayer Compliance AT KPP Pratama Medan Timur - Putri Wahyuni; Susan Grace Veranita Nainggolan (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine whether the Whistleblowing System and Tax Sanctions have a significant effect on individual taxpayer compliance at KPP Pratama Medan Timur. This study uses quantitative data types and data sources are primary data. The population in this study is an individual taxpayer who pays an annual tax return to the KPP Pratama Medan Timur. The analytical method used in this study is multiple linear regression using SPSS program. The results partially show that the Whistleblowing System has a significant effect on taxpayer compliance at KPP Pratama Medan Timur. The results partially show the Tax Sanctions has a significant effect on taxpayer compliance. The results of the study simultaneously showed that Whistleblowing System and Tax Sanctions has a significant effect on taxpayer compliance a KPP Pratama Medan Timur. . The coefficient of determination (R Square) means that the Taxpayer Compliance variable can be explained by the Whistleblowing System variable and Tax Sanctions and the remaining Taxpayer Compliance variable is explained by other variables not included in the study.